2020
DOI: 10.1109/tsg.2019.2950115
|View full text |Cite
|
Sign up to set email alerts
|

Fast Calculation of Probabilistic Power Flow: A Model-Based Deep Learning Approach

Abstract: Probabilistic power flow (PPF) plays a critical role in the analysis of power systems. However, its high computational burden makes practical implementations challenging. This paper proposes a model-based deep learning approach to overcome these computational challenges. A deep neural network (DNN) is used to approximate the power flow calculation process, and is trained according to the physical power flow equations to improve its learning ability. The training process consists of several steps: 1) the branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…The performance differences among neural networks with various structures are compared, and three kinds of power bus systems are used for evaluation benchmark. Compared with the pure datadriven deep learning method, the proposed method can comprehensively improve the approximate accuracy and training speed [26]. Compared with the current situation that learning-based approaches are mostly proposed to identify and evaluate system situations, Su proposes a power system control method with deep belief network [27].…”
Section: Related Workmentioning
confidence: 99%
“…The performance differences among neural networks with various structures are compared, and three kinds of power bus systems are used for evaluation benchmark. Compared with the pure datadriven deep learning method, the proposed method can comprehensively improve the approximate accuracy and training speed [26]. Compared with the current situation that learning-based approaches are mostly proposed to identify and evaluate system situations, Su proposes a power system control method with deep belief network [27].…”
Section: Related Workmentioning
confidence: 99%
“…To quantifying the impact of the correlation among multi-dimensional wind farms on the power system, Zhu proposes a probabilistic power flow calculation framework with learning-based distribution estimation approach [16]. Yang et al propose a model-based deep learning approach to quickly solve the power flow equations, with the main application of speeding up probabilistic power flow calculations [17]. Compared with the pure data-driven deep learning method, the proposed method can comprehensively improve the approximate accuracy and training speed.…”
Section: Related Workmentioning
confidence: 99%
“…Some studies have also explored embedding physical characteristics within deep learning methods. A physics-guided neural network approach was proposed in [63] to calculate probabilistic power flow. The training process was improved by the grid characteristics, and the case study showed a great computation speedup.…”
Section: Category 3 Surrogate Modelmentioning
confidence: 99%